ZELDAS: Pemanfaatan Zeolit Sintesis Berbahan Dasar Limbah Sekam Padi Sebagai Pengurai Merkuri dengan Penambahan Karbon Aktif dari Limbah Tempurung Kelapa Sebagai Upaya Reklamasi Lahan Bekas Tambang Emas - Aulia Akmal, Amaajid; Fadhil Kresna Hidayat; Agus Widayoko; Dwi Atmoko, Indrato (SMA Trensains Muhammadiyah Sragen, 2025)
Indonesia's high productivity of gold mining has increased the use of mercury, the use of mercury in the gold mining industry in Indonesia reaches 13.94-192.53 tons per year. Mercury is a highly toxic chemical element (toxic) the toxic nature of mercury can endanger human life as well as the surrounding environment. Conventional reclamation methods such as phytoremediation have limited time and efficiency in restoring mercury-contaminated land. This research focuses on making ZELDAS which is an innovative solution based on synthesized zeolite from rice husk waste and activated carbon from coconut shell, to accelerate the recovery of mercury contaminated land. ZELDAS is made through the process of synthesizing sodium silicate and sodium aluminate from rice husk ash, then combined with activated carbon from coconut shell activation. The research method used descriptive qualitative method because ZELDAS is a qualitative product and data acquisition using literature study and observation. Tests included pH, density, mercury adsorption, and soil fertility tests. The results showed that ZELDAS has a pH of 7, a density of 1.27 g/cm³, and an adsorption capacity of 87.24%, indicating its effectiveness in absorbing heavy metals. Soil fertility tests showed that soil treated with ZELDAS was able to grow plants up to 10 cm in 14 days, faster than the phytoremediation method. With its high efficiency and economical cost, ZELDAS is a potential alternative for reclaiming mined land. This study recommends large-scale testing and development of application technology for wider implementation.